Insecticide susceptibility of Aedes aegypti and Aedes albopictus in Central Africa - (:unkn) unknown (My University, 2011)
Background: Aedes aegypti (Linnaeus, 1762) and Aedes albopictus (Skuse, 1894) are the main vectors of dengue (DENV) and chikungunya (CHIKV) viruses worldwide. As there is still no vaccine or specific treatment for DENV and CHIKV, vector control remains the cornerstone of prevention and outbreak control. Unfortunately, vector control programs are facing operational challenges with mosquitoes becoming resistant to commonly used insecticides in several areas through the world. Throughout Central Africa no recent data are available susceptible/resistant status of either vector species since the introduction/arrival of Ae. albopictus in this area. We therefore studied the level of resistance of these two major vectors to insecticides commonly used in Africa for mosquito control.Results: Aedes aegypti and Ae. albopictus were sampled in six urban localities of Cameroon (Garoua, Bertoua, Yaoundé, Bafia, Buea) and Gabon (Libreville). Larval bioassays, carried out to determine the lethal concentrations (LC50 and LC95) and resistance ratios (RR50 and RR95) suggested that both vector species were susceptible to Bti (Bacillus thuringiensis var israeliensis) and temephos. Bioassays were also performed on adults using WHO diagnostic test kits to assess phenotypic resistance to deltamethrin, DDT, fenitrothion and propoxur. These experiments showed that one population of Ae. aegypti (Libreville) and two populations of Ae. albopictus (Buea and Yaoundé) were resistant to DDT (mortality 36% to 71%). Resistance to deltamethrin was also suspected in Ae. albopictus from Yaoundé (83% mortality). All other field mosquito populations were susceptible to deltamethrin, DDT, fenitrothion and propoxur. No increase in the knockdown times (Kdt50 and Kdt95) was noted in the Yaoundé resistant population compared to other Ae. albopictus populations, suggesting the possible involvement of metabolic resistance to deltamethrin and DDT.Conclusion: In view of the recent increase in dengu
Keywords: African Research